Ecologizing Nature Among (Not Quite) Secular Northerners: Special Issue Editors' Introduction - Rubow, Cecilie (Journal for the study of religion, nature and culture, 2025)
If modernization is a process of compartmentalization, then ecologization is its opposite. This is the opening idea of this special issue, borrowed from Bruno Latour's paper "To Modernize or to Ecologize? That’s the Question" from 1998. In this text, Latour's invitation is to take steps toward reconnecting nature, that is, the landscapes, other species, the environment, with the cultural in its political, existential, emotional and spiritual dimensions of our societies.